Effect of Hedonism Lifestyle and Emotional Intelligence on Personal Financial Management in Student of STIEM Bongaya Makassar - Chaerunnisa Rumianti (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze effect of hedonism lifestyle and emotional intelligence on personal financial management in student of STIEM Bongaya Makassar. The type of research approach used in this research is quantitative research. The population in this study are all undergraduate students majoring in management at STIEM Bongaya Makassar class 2018 who are registered as active students as many as 799. By using a margin of error of 10%, the sample size are 89 students. Data analysis using t test (partial). The results show that hedonism lifestyle has a positive and significant effect on personal financial management in student of STIEM Bongaya Makassar. Emotional intelligence has a positive and significant effect on personal financial management in student of STIEM Bongaya Makassar.